Reconstructing the State's Right of Control Paradigm from a Prophetic Law Perspective - Dian Aries Mujiburohman (Marcapada: Jurnal Kebijakan Pertanahan, 2026)
The interpretation of the State's Right to Control (HMN) in agrarian law is still dominated by a positivistic approach that positions the state as the center of authority over land, while the ethical dimensions underlying the use of that authority have not received adequate attention. This paper re-examines HMN from a prophetic legal perspective using normative legal research and statutory, conceptual, and philosophical approaches. The study indicates that the UUPA not only regulates state authority in the agrarian sector but also contains the values ​​of transcendence, humanization, and liberation that form a unity. Transcendence views the state as the recipient of the mandate to manage agrarian resources, not as the landowner. Humanization requires that the implementation of HMN respect human dignity through the social function of land and the protection of community rights. Liberation directs state authority to reduce inequality in land ownership, expand access to agrarian resources, and realize agrarian justice. Based on these findings, this paper proposes the Prophetic Triangle Concept of the Right to Control, a conceptual model that integrates transcendence as a source of moral legitimacy, humanization as a principle for the implementation of authority, and liberation as the ultimate goal of agrarian management. This concept offers a new reading of the right to control by shifting its orientation from a paradigm of control to a paradigm of a just mandate.